PENGARUH PEMBERIAN KOMPOS AMPAS TAHU DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TERUNG UNGU (Solanum melongena L.) - Nuraida; Arnis En Yulia (UIR Press, 2022)
This research aimed to examine the effective interaction of tofu waste compost and NPK fertilizer to determine the best doses which give the growth and highest production of purple eggplant. The research was conducted at Experimental Farm, Faculty of Agriculture, Riau University, Pekanbaru. The research was conducted for 5 months, from February to June 2020. The research was experimentally arranged in a 3x3 factorial using a completely randomized design (CRD). The first factor was the tofu waste compost consisting of 3 levels (0, 10, and 20 tons.ha-1). The second factor was the NPK fertilizer (0, 100, and 150 kg.ha-1) which consists of nine treatments combination. The observed parameters were the height of the plant, the days of flowering, the days of harvesting, the fruit length, the fruit diameter, the number of fruits per plant, the fruit weight per fruit, the fruit weight per plant, and the fruit weight with the plot. The data in this research was analyzed using variance and followed by Duncan's multiple distance test at a 5% level. The results showed that tofu waste compost and NPK fertilizer increased the growth of eggplant such as the height of the plant, the days of flowering, the days of harvesting, the number of fruits per plant, the fruit length, the fruit weight per fruit, the fruit weight per plant and the fruit weight with plot and does not increase fruit diameter. The giving tofu waste compost at a dose of 20 tons.ha-1 and NPK fertilizer 150 kg.ha-1 gave the best eggplant growth and production until the plants were 90 DAP.